Impact of severe dysphagia on overall survival after percutaneous endoscopic gastrostomy - Kazumi Shimamoto; Ryota Matsui; Yorihiro Nishiyama; Kyohei Nishino; Hiromitsu Ban (Scientific Reports, 2025)
Abstract In this study, we investigated the effect of severe dysphagia on the overall survival of patients who underwent PEG. A cohort of patients who underwent PEG between April 2016 and April 2021 was retrospectively analyzed. The Hyodo–Komagane score was used to evaluate swallowing via endoscopy. Patients with a Hyodo–Komagane score ≤ 8 were defined as having moderate dysphagia, whereas those with a score ≥ 9 were defined as having severe dysphagia. The primary outcome was overall survival. The prognostic factors were identified using multivariate analysis with the Cox proportional hazards model. Values of p < 0.05 were considered statistically significant. Among the 107 patients, 60 (56.1%) were classified into the moderate dysphagia group and 47 (43.9%) into the severe dysphagia group. The median follow-up period was 16.7 months. The overall survival was significantly worse in the severe group than in the moderate group (p < 0.0001). A multivariate analysis revealed that severe dysphagia was an independent poor prognostic factor (hazard ratio, 2.956; 95% confidence interval, 1.592–5.489; p < 0.001). Aspiration-related pneumonia was most common causes of death after PEG. Severe dysphagia was identified as an independent poor prognostic factor for survival in patients who underwent PEG.